PENGARUH MEDIA ROULETTE TERHADAP MINAT IBU DALAM PEMERIKSAAN IVA (INSPEKSI VISUAL ASAM ASETAT) DI POSYANDU KELURAHAN PAKISTAJI KOTA PROBOLINGGO - Dewi, Selvi Prabandari Purnama; Safitri, Rani; Ilmiah, Widia Shofa (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Cervical cancer is also called cervical cancer. Based on data from WHO, cancer is the leading cause of death in the world, also lurking in Indonesia. Cervical cancer can be detected early by conducting an IVA (Visual Inspection of Acetic Acid) examination. However, the mother who did the IVA examination in Pakistaji Village was not there at all. The purpose of the study was to determine the effect of roulette media on mother’s interest in IVA (Visual Inspection of Acetic Acid) examination at Integrated Service Post, Probolinggo City The type of research used was an experimental type with a pre-post test design type. The population in this study is all mothers registered at the Pakistaji Integrated Service Post, Probolinggo City in September 2023, amounting to 69 people. The sampling technique with simple random sampling with a sample of 16 respondents. The research instrument used questionnaire sheets. Data analysis using the Wilcoxon Sign Rank Test in the control group that Z was calculated at - 3.578 with a sig value of 0.05 and obtained a p-value of 0.000. So it can be concluded that the p-value is smaller than the sig value (0.000 0.005) which means that Ha is accepted, namely there is an influence of roulette media on maternal interest in IVA (Acetic Acid Visual Inspection) examination at the Integrated Service Post, Probolinggo City. Roulette media can be used as a reference in health counseling about IVA and is expected to motivate, add information, and increase respondents' awareness to conduct IVA (Visual Inspection of Acetic Acid) examination as an effort to detect early cervical cancer. Conducting an IVA (Visual Inspection of Acetic Acid) examination so that the sooner the problem is found, the faster the case will be handled.